Jaminan Sosial Tenaga kerja Bagi Mahasiswa Magang Profesi Pada Perguruan Tinggi Implementasi dari Undang-Undang Ketenagakerjaan - Ronny Soplantila (Faculty of Law, Universitas Pattimura, 2019)
Higher education will send final semester students to internships in government agencies and private companies to provide experience before entering the workforce, but in practice never pay attention to the form of protection for students, while the labor law provides space for student interns to enter into workforce social security program, for this purpose the purpose of this study is to examine whether student internships can be equated with workers and are entitled to workforce protection. Guaranteed labor protection for intern students is very important both for intern students, universities and government agencies and private companies. Because it will protect students, comfort for family students and universities will feel free from moral burdens in the event of work accidents in government agencies and private companies where the student is placed.